Healing the Wounded to Lead in the Postcolonial Church - Pieter Labuschagne (Ecclesial Futures, 2024)
Amidst calls for decolonization and Africanization in theological reflection on the African continent, this paper looks at the long-lasting effects of colonialism, its power, and the inequalities and vulnerabilities it created, and how, long after the demise of the structures of colonialism, the coloniality of the heart still lingers.